Ways to understand India: The Czech experience - Vavroušková, Stanislava (Acta Orientalia Vilnensia, 2008)
Oriental Institute of the Czech Academy of Sciences To promote and further the understanding of India in the Czech Republic, Czech Indologists (in addition to their academic activities) publish articles, analyses and books on Indian history, culture and politics in the Czech language and deliver lectures intended for the general public. They continue in the tradition of the founders of Czech Indian studies (e.g. Vincenc Lesný, Moritz Winternitz), who were active in the first half of the 20th century. The Indian Association, founded in 1934 and affiliated with the Oriental Institute in Prague, promoted mutual contacts between India and Czechoslovakia and organised visits of prominent Indians (e.g. R. Tagore, J. Nehru, S. Ch. Bose) to Czechoslovakia in the years prior to World War II. The Friends of India Association (founded 1990) offers public lectures and organises exhibitions of Indian art, performances of Indian artists, and occasionally, courses of Indian languages. In close cooperation with the academic community, the association tries to provide unbiased, balanced information on India which is based on academic research, personal experience, and very often, life-long dedication to the country and its people.